MEASURING THE TIC IMPACT ON THE ACCOUNTING PROFESSION TEACHING - Villanueva Ipanaqué, Carmen Isabel (2016)
The present research seeks to answer the question: What is the measurement model to assess the impact of the ICT use in the teaching-learning process to obtain a formative improvement of public accountants in national universities of Lima Metropolitan Area? The work addresses this subject and bases its proposal on the theories of teaching, learning and continuous improvement. That starts with a cross descriptive non-probabilistic analysis methodology with a field design. A survey was applied consisting of 40 closed questions, stablished with the Likert scale and validated by the experts judgment. The results of the research can be summarized as follows: (a) The existence of ICTs in national universities allows them to optimize their teaching skills and learning, (b) the national universities that have implemented ICT are able to promote formative continuous improvement of Public Accountants. (C) Measuring the impact of ICT contributes to the creation of competitive advantages in technological capabilities of national universities.